From Matching to Making: A Canvas for Collaborative Circular Value Creation - Whalen, Katherine A.; Renström, Sara (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Co-design, which involves end-users in the design process, has emerged as a promising strategy for developing circular offerings. However, creating such offerings requires collaboration not only with end-users but also between companies forming circular ecosystems centered on shared value propositions. While existing research highlights the importance of inter-company collaboration and co-design with end-users, tools supporting co-creation with both users and multiple stakeholders remain limited. This paper introduces and evaluates a prototype tool called the Collaborative Circular Value Creation Canvas. The tool is designed to facilitate company collaboration in generating concepts for circular offerings, which can serve as structured inputs for co-design with end-users. This paper reports on testing the canvas in a pilot workshop. Initial findings suggest the tool's potential to foster inter-company collaboration and generate valuable inputs for a co-design process with end-users. However, further research is needed to validate its role in a co-design process and its ability to foster business models focused on product longevity. Additionally, the implications of using the tool in a digital format should be further investigated.